The role of modern Jadid scholars in the development of schools of translation studies. (Journal of Pedagogical Inventions and Practices, 2022)
This article talks about the importance of translation studies today and the contribution of representatives of the Jadid movement to the development of schools of translation studies, and the examples of the works they translate reveal the range of skill of the leading representatives, the 20th century is depicted. It also discusses the importance of translated works for other indigenous peoples and ways to further develop this area.